Silata na ženskoto slovo v baladite na K.J. Erben - Madžarova, Tanja (Wydawnictwo Naukowe UAM, 2013)
The power of women’s words in K.J. Erben’s ballads discusses the author’s literary texts (the collections Písně and Kytice), in which the woman is presented as a permanent character who is in the focus of significant conflict situations and moral problems. Women’s words have a broad spectrum of expression: from the intimate address to oneself, through the prayer, the blessing, the divination, and the imprecation, to the prophecy. Women’s words refer to a peculiar reflection of the collective memory and norm, but at the same time they bring the woman out of her anonymity, individualizing her in her own desires and intentions.
The Power of Women’s Words in K.J. Erben’s Ballads
Keywords: speech of the woman; prayer; blessing; divination; imprecation; collective memory